FEATURES AND STRUCTURE OF A SPECIAL TYPE OF NOVEL PROSE OF THE GENRE "FAMILY CHRONICLE" - Lokteva Nadezhda Mikhailovna (Galaxy International Interdisciplinary Research Journal, 2021)
The purpose of the study is to determine the features and structure of a special type of novel prose of the Family Chronicle genre. The scientific novelty of the work lies in the approach to the study of the works of the American family chronicle of the 19th century. from the point of view of their genre originality, family relations, the psychology of behavior, the character of the characters in the work are shown. As a result, it was revealed that in family chronicles clashes of characters, positive initial data, and a high "vocation" in the New and Old Worlds are explored.